ZOONOTIC VIBRIO DIVERSITY AND DISEASES IN MUDCRAB FISHERY: IMPACTS ON PUBLIC HEALTH IN INDIA - SAHA, SANJIB; DASH, GADADHAR (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2021)
Aquaculture of Scylla sp. (Mudcrab) at present is an emerging, demanding and alternative fishery farming with respect to socio-economic evaluation in India due to high nutritional value (large size, high quantity meat content and good source of protein and calcium ions) and export value, (local as well as foreign market). A large portion of coastal people of India (West Bengal and South India) involve in mud crab fishery for their livelihood. Mass mortality in Scylla sp. is very common in India due to Vibrio sp. infection (Vibriosis) and Vibrio infected mud crabs may potentially transmit toxic genes as zoonotic strains in other organism including human. The following symptoms in human beings such as fever, chills, nausea, hypotensive septic shock, secondary lesion, infection, gastroenteritis and diarrhea are very common. Natural habitat of Mudcrab and cultured firm become contaminated with different opportunistic Vibrio sp. by various known and unknown sources and Mudcrab stock in brackishwater become gradually decline due to high salinity, temperature, pH. Such climatic as well as bio-unsafe environment also helps to multiply of Vibrio natural way and spread zoonotic diseases frequently in human through wounding, handling and consumption. In order to ensure a productive Scylla sp. aquaculture and to reduce the incidence of diseases without mass mortality, need to diagnose the pathogenic infection accurately before spreading. This paper review the zoonotic diseases of Vibrio sp. and its impact on human health and livelihood.